Determination of the Initial Thickness of a Tubes to Bending. Part I. Derivation of the Basic Expressions and Relationships. Part II. Discussion and Analysis of Obtained Results - ŚLODERBACH, Zdzisław (Engineering Transactions, 2015)
In this second part of the paper, applying epressions derived in Part I, the exemplary calculations of the initial thickness of a metallic tube subject to bending at bending machines are presented. The expressions for calculating of the initial thickness were presented for a suitable measure of the big actual radius Ri in the bending zone for an exact (general) solution and for three formal simplifications of the 1st, 2nd, and 3rd order. In the calculations the external or internal diameter of the tube subjected to bending is applied as a parameter. In this paper, the author shows that the calculated initial thickness of the tube (for the same parameters ofbending) depending on the external diameter is lower than that calculated depending on the internal diameter. For example, the expression for calculation of deformations included in the UE Directive [1], contains dependence on dext not on dint. The results of the calculations are presented in the graphs and tables enclosed.